1999
DOI: 10.2134/agronj1999.916902x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Overseeded Alfalfa and Bermudagrass to Alfalfa Row Spacing and Nitrogen Rate

Abstract: Alfalfa (Medicago sativa L.) is a rare forage crop on Coastal Plain soils. Acid soils, wet conditions, and the prevalence of perennial, warm‐season grasses limit alfalfa production. Development of grazing‐tolerant varieties raised interest in growing alfalfa on the Coastal Plain. This three‐year dryland field study was conducted to evaluate coincident production of ‘Alfagraze’ alfalfa and ‘Coastal’ bermudagrass [Cynodon dactylon (L.) Pers.] as a sustainable forage system. Limestone (effective calcium carbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 13 publications
3
35
0
Order By: Relevance
“…In the humid eastern United States, fertilizer recommendations based on soil test results indicate the need for K application (11), particularly in low buffer capacity, acid sandy soils testing low to medium in plant-available K. Coarse-textured soils sometimes are better suppliers of K for plant growth than would be expected based on exchangeable K concentrations (12). Splitting 372 kg K ha 21 at rates of onehalf each in fall or spring, or one-fourth for each cutting, starting in early spring, did not increase the 3-yr average yields of alfalfa on a loam soil at a yield level of 17 Mg ha 21 (13). Calcitic and dolomitic limestones are the principal sources of Ca, and dolomitic limestone supplies Mg when applied to acid soils.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…In the humid eastern United States, fertilizer recommendations based on soil test results indicate the need for K application (11), particularly in low buffer capacity, acid sandy soils testing low to medium in plant-available K. Coarse-textured soils sometimes are better suppliers of K for plant growth than would be expected based on exchangeable K concentrations (12). Splitting 372 kg K ha 21 at rates of onehalf each in fall or spring, or one-fourth for each cutting, starting in early spring, did not increase the 3-yr average yields of alfalfa on a loam soil at a yield level of 17 Mg ha 21 (13). Calcitic and dolomitic limestones are the principal sources of Ca, and dolomitic limestone supplies Mg when applied to acid soils.…”
Section: Introductionmentioning
confidence: 88%
“…Increasing N rates split applied for each bermudagrass growth period significantly increased bermudagrass dry matter at yield levels that declined annually but had little effect on total annual yield of alfalfa dry matter production on a Darco loamy fine sand (21). Applied N significantly increased alfalfa dry matter production at specific harvests.…”
Section: Nitrogenmentioning
confidence: 96%
See 2 more Smart Citations
“…Most of these growers were attracted to alfalfa because they have seen enormous improvement in the quality of their hay, and they were able to save on the application of nitrogen fertilizer. Studies evaluating the sustainability of production of alfalfa interseeded in bermudagrass showed that alfalfa competes well with bermudagrass, even in drought conditions [11]. Another part of the forage system in the region is cereal rye that is grown for late fall and early winter grazing when bermudagrass goes dormant.…”
Section: Introductionmentioning
confidence: 99%